MEMAKSIMALKAN PERANAN WANITA DALAM PEREKONOMIAN RUMAH TANGGA PADA DESA KUIN BESAR - Yuliani Yuliani; Neti Rosiana Fadilah; Muhammad Fahmi; Jamaluddin Jamaluddin; Julia Anggraeni; Eyen Rosalina (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2026)
The economic condition of households is currently in a challenging phase due to inflation in basic commodity prices and a decline in people's purchasing power. This issue is also experienced by the community of Kuin Besar Village, where the majority relies on fisheries, wetland agriculture, and local trade for their livelihoods. This study aims to educate and maximize the role of women or housewives as strategic partners in improving family economies and financial resilience. The implementation method was divided into three stages: the preparation stage (schedule coordination and literature study), the execution stage (oral or face-to-face material delivery and Q&A discussion), and the evaluation stage (distribution of a small questionnaire to measure community understanding and commitment). The results and discussion show that women's involvement in public and economic spheres, both through family financial management (internal) and as income earners in formal and informal sectors such as mompreneurship in the digital era (external), is a strategic pillar in diversifying household income. In conclusion, the urgency of women's role in improving the family economy is no longer just an option, but a strategic necessity to achieve independence, child welfare, and family resilience against economic shocks..